Studying the diversity of Central African harps 1 - (:unkn) unknown (My University, 2025)
Human societies share the ability to develop cultural traits and to make them evolve in different geo-cultural environments. 3 Given the geographical dispersion of human societies and their vast cultural diversity, these changes are variable depending on both the populations in question and the nature of the cultural domains being studied. The mechanisms involved in the transformations of cultural artefacts are still relatively poorly understood. 4 While it is easily possible to describe the diversity and therefore the results of cultural evolution at a given moment, the processes established by human societies to culturally distinguish themselves from one another have been little studied to date. Music and language are two of the cultural domains shared by all human communities on the planet. Musical instruments are the material witnesses of the musical practice of human communities, be they of oral or written traditions. Few studies are yet devoted to geo-cultural area-specific comparisons in order to understand the existing diversity and variability in musical instruments. This is even more true in societies with an oral tradition, where studies can usually only be based on an analysis of the objects with incomplete information -either because this 236 1 The data for this article have been collected thanks to the financial support of several institutions: fieldwork in Gabon (Sylvie Le Bomin, 2017 to 2019) and documentary research in the museum collections and the private collections by the Muséum National d'Histoire Naturelle (Action Thématique du Muséum programme Kundi), the Labex BcDiv and the Alliance Sorbonne Universités directly (GeacMus Chair and the Emergence programme Kundi).
Keywords: African Research